OFFSET ON THE MAIN RECENT FAULT OF NW IRAN AND IMPLICATIONS FOR THE LATE CENOZOIC TECTONICS OF THE ARABIA-EURASIA COLLISION ZONE - Talebian M.; Jackson J. (My University, 2002)
We use drainage patterns, geological markers and geomorphological features to determine a right-lateral offset of ∼50 km, and possibly as much as ∼70 km, on the Main Recent Fault in NW Iran. This fault trends NW–SE and forms the NE border of the Zagros mountains. It accommodates the strike-slip component of the N–S convergence between Arabia and Eurasia, with the NE–SW shortening component being accommodated in the Zagros Fold Belt. Its ∼50 km strike-slip offset implies a shortening of ∼50 km in the fold belt and ∼70 km total N–S convergence accommodated in the NW Zagros. This is a substantial fraction of the 85–140 km overall Arabia–Eurasia convergence expected over the last 3–5 Ma. If the Main Recent Fault initiated at that time, as seems likely from geological arguments, it has a horizontal slip rate of at least 10–17 mm yr−1 and should be the source of frequent earthquakes of Ms 6–7, as has been seen in the 20th century and the earlier historical record. The similarity of the offsets and probable ages of the North Anatolian and Main Recent Faults suggests that they have been active as an almost continuous zone of right-lateral shear on the north edge of the Arabian and Anatolian plates since the early Pliocene.
Keywords: Cenozoic; Cenozoic; Кайнозой